2020
DOI: 10.1293/tox.2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline protects against acrylamide-induced neurotoxicity and testicular damage in Sprague-Dawley rats

Abstract: This study investigated the protective effects of minocycline against acrylamide (ACR)-induced neurotoxicity and testicular damage in Sprague-Dawley rats. Forty rats were divided into five groups (eight rats each). Group I received saline (0.5 mL/rat) daily for 10 days and served as the untreated control group. Group II received ACR (30 mg/kg body weight (b.w.)) daily for 10 days. Group III received ACR (30 mg/kg b.w.) daily for 10 days and subsequently minocycline (60 mg/kg b.w.) for five days. Group IV recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Acrylamide (ACR) is a highly toxic chemical with ubiquitous applications in plastic and paper production, dyes and water treatment (Radad et al, 2020). It is a monomer used in laboratories for preparation of polyacrylamide gel for electrophoresis and chromatographic techniques (Kirley & Norman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Acrylamide (ACR) is a highly toxic chemical with ubiquitous applications in plastic and paper production, dyes and water treatment (Radad et al, 2020). It is a monomer used in laboratories for preparation of polyacrylamide gel for electrophoresis and chromatographic techniques (Kirley & Norman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Also Khaled Radad et al reported in a study that Minocycline improved neuronal degeneration and seminiferous tubular damage and reduced malondialdehyde levels. To sum up, minocycline deflect neurotoxic effects of acrylamide and seminiferous tubular damage, which might be due to reduced lipid peroxidation (Radad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It can move across the BBB and exhibit its therapeutic efficiency [36,68,69]. Other compounds like metformin, minocycline and zolpidem also show similar therapeutic effects to dietary supplements when administered to ACR-treated rats [70][71][72] (Table 2).…”
Section: Phytochemicalsmentioning
confidence: 98%